2009
DOI: 10.1111/j.1440-1681.2008.05122.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Mitochondrial Permeability Transition, Glutathione Status, Pentose Phosphate Pathway and Oxidative Damage in the Protective Effect of Fasting on the Ischaemic‐reperfused Rat Heart

Abstract: 1. Fasting, which increases the catabolism of fatty acids, gives functional protection to the ischaemic-reperfused heart. To obtain further knowledge of this cardioprotective effect, changes in mitochondrial permeability transition (MPT) were measured by the entrapment of 2-deoxy-[(3)H]-glucose (2-DG). We also assessed whether MPT is associated with changes in glutathione status, the activity of glucose-6-phosphate-dehydrogenase (G6PDH) and tissue oxidative damage, estimated by the measurement of Thiobarbituri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Though prolonged caloric limitation is a well-established protective stimulus, effects of brief or moderate fasting await detailed study in DM animals. Severe CR for 11 days generates unique I–R tolerance [ 490 ], and 24–72 h of fasting enhances cardiac I–R tolerance and mitochondrial viability in non-DM hearts [ 491 , 492 ]. There are surprisingly few studies of caloric limitation in DM.…”
Section: Potential ‘Membrane-targeted’ Therapies?mentioning
confidence: 99%
“…Though prolonged caloric limitation is a well-established protective stimulus, effects of brief or moderate fasting await detailed study in DM animals. Severe CR for 11 days generates unique I–R tolerance [ 490 ], and 24–72 h of fasting enhances cardiac I–R tolerance and mitochondrial viability in non-DM hearts [ 491 , 492 ]. There are surprisingly few studies of caloric limitation in DM.…”
Section: Potential ‘Membrane-targeted’ Therapies?mentioning
confidence: 99%
“…KEGG indicated that signaling pathways were enrichment in methylation modification pattern B (Supporting Information: Figure ), including Cytochrome P450, Glutathione Metabolism, Ribosome, Proteasome, Arachidonic Acid Metabolism, Base Excision Repair and Pentose Phosphate Pathway. Since the activation of the seven signaling pathways was associated with DCM risk (Ganapathi et al, 2020; Kanoh et al, 1999; Lei et al, 2009; Lu et al, 2012; Marina Prendes et al, 2009; Spänig et al, 2019; Zhou et al, 2016), it indicated that methylation modification pattern B (but not methylation modification patterns A and C) was more likely linked to the risk of DCM. In addition, the Venn diagram revealed that 501 genes were involved in m6A methylation modification (Supporting Information: Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…RNA modification exists in all living forms, and more than 150 RNA modifications have been identified, including N1-methyladenosine (m1A), 5-methylcytosine (m5C), and N6-methyladenosine (m6A), in which, m6A methylation is the most prevalent RNA modification and is mediated by various m6A regulators (Patil et al, 2016). Since m6A RNA methylation has impact on immunocyte function and disturb antitumor immunity (Han et al, 2019;Ma et al, 2021), we speculate that m6A RNA methylation may involve in the immune microenvironment disorder. This study is to explore the role and mechanisms of m6A-related immune microenvironment disorder in the development of DCM.…”
mentioning
confidence: 99%
“…In addition to these insights, the ability of caloric restriction or fasting to protect against IR-induced injury is associated with decreased MPTP opening and increased respiratory function, increased activity of NADPH-generating glucose-6-phosphate dehydrogenase (G6PDH) and attendant increases in GSH/GSSG redox, and decreased biomarkers of oxidant stress [35,164,316] (Figure 7). It is interesting that short-term fasting has been found to confer similar protection against IRI as more long-term caloric restriction [35,440,532], as does chronic, but intermittent fasting [229].…”
Section: Caloric Restrictionmentioning
confidence: 99%